During forearm rotation the three-dimensional ulnolunate distance is affected more by translation of the ulnar head than change in ulnar variance. (June 2019) - Shin, Seung-Han; Lee, Yong-Suk; Choi, Keun-Young; Kwak, Dai-Soon; Chung, Yang-Guk
Ulnolunate abutment has been thought to be aggravated by pronation because of an increase in ulnar variance. We hypothesized that the ulnolunate distance might be greater in pronation because the ulnar head is dorsally translated. Twenty-one three-dimensional reconstructions of computed tomographic scans of wrists taken in supination and pronation were investigated. The ulnolunate distance was measured in each position, and the change in ulnolunate distance from supination to pronation was calculated. The changes in ulnar variance from supination to pronation and the amount of translation of the ulnar head were measured directly by superimposing three-dimensional reconstructions. The mean ulnolunate distance in pronation was significantly greater than in supination. There was no significant correlation between the changes in ulnolunate distance and in the ulnar variance. The change in ulnolunate distance had a significant positive linear relationship with the amount of translation of the ulnar head. The change in ulnolunate distance during forearm rotation is determined by the amount of translation of the ulnar head rather than by change in ulnar variance. Level of evidence: IV